A New Centimeter‐Sized Ti‐Based Quaternary Bulk Metallic Glass with Good Mechanical Properties1. Issue 8 (18th March 2013) - Gong, Pan; Yao, Kefu; Wang, Xin; Shao, Yang
Abstract We report a new Ti40Zr26Be28Fe6 bulk metallic glass designed by slightly decreasing Ti/Zr concentration ratio based on the newly developed Ti41Zr25Be28Fe6 bulk metallic glass. The Ti40Zr26Be28Fe6 glassy alloy exhibits high thermal stability and the width of the supercooled liquid region for this alloy is up to 100 K. By conventional copper mold suction casting method, Ti40Zr26Be28Fe6 fully glassy rod with a diameter of 10 mm can be successfully obtained. Ti40Zr26Be28Fe6 glassy alloy also possesses excellent mechanical properties such as a high specific strength of 4.03 × 105 Nm kg−1 and an obvious compressive plastic strain of 7.4%, which make it possible to be used as novel aerospace materials.